Role of Cell-Free DNA in Relapsed Head and Neck Cancer - Annie Kanchan Baa; Atul Sharma; Mayank Singh; Ashna Gupta; Ahitagni Biswas; Sacchidanand Jee Bharti; Alok Thakar; Rajeev Kumar; Raja Pramanik (Indian Journal of Medical and Paediatric Oncology)
Introduction Owing to the aggressive biology of head and neck squamous cell carcinoma (HNSCC), new biomarkers that can facilitate the diagnosis and tracking of tumour growth are the need of the hour. Liquid biopsy has emerged as an easier tool than tissue biopsy to monitor the emergence of treatment resistance or the recurrence of disease at the molecular level.